High-contrast 3D in vivo microvascular imaging using scanning 2D ultrasound and acoutic sub-aperture processing (ASAP) - Hau,Leow C; Bush,NL; Stanziola,A; Braga,M; Shah,A; Hemández-Gil,J; Long,NJ; Aboagye,EO; Bamber,JC; Tang,MX (IEEE, 2019)
Non-invasive techniques for microvascular environment assessment are invaluable for clinical diagnosis and treatment monitoring. We recently developed a super contrast processing to suppress noise background in ultrafast Power Doppler, known an acoustic sub-aperture processing (ASAP), and demonstrate using 2D contrast enhance ultrasound. However, 2D imaging is insufficient to represent the 3D complex vascular environment. We therefore extend our study to demonstrate the feasibility of our technique for volumetric imaging. A pseudo-3D imaging technique was developed and demonstrated using a research system and preclinical transducer. A mouse liver was scanned using 2D ultrafast ultrasound and a mechanical translation stage. Initial results not only demonstrated a substantial noise reduction in 2D vascular images using ASAP, but also a high contrast volumetric rendering of a mouse liver. Our technique is ready for clinical use to provide better evaluation of angiogenesis.